Plant strategies in relation to resource supply in mesic to wet environments: does theory mirror nature? - Ordoñez, Jenny C; van Bodegom, Peter M; Witte, Jan-Philip M; Bartholomeus, Ruud P; van Hal, Jurgen R; Aerts, Rien (The American naturalist, 2010)
In ecology, strategy schemes based on propositions about the selection of plant attributes are common, but quantification of such schemes in relation to nutrient and water supply is lacking. Through structural equation modeling, we tested whether plant strategies related to nutrient and water/oxygen supply are reflected in a coordination of traits in natural communities. Structural equation models, based on accepted ecological concepts, were tested with measured plant traits of 105 different species across 50 sites in mesic to wet plant communities in the Netherlands. For each site, nutrient and water supply were measured and modeled. Hypothesized multivariate strategy models only partly reflected current theoretical schemes. Alternative models were consistent, showing that lack of consistency of the original models was because of (i) strong correlations among traits that supposedly belong to different strategy components; (ii) poor understanding of mechanisms determining the covariation of plant maximum height, leaf size, and stem density; and (iii) lack of integrative and long-term measures of nutrient supply needed to predict coordinated plant trait responses. Our main conclusion is that a combination of trade-offs (partly) across different plant organs and diverging effects of resource supply ultimately determines the coordination of plant traits needed to "make a living."